2003
DOI: 10.1101/gad.1062303
|View full text |Cite
|
Sign up to set email alerts
|

How does an axon grow?

Abstract: How do axons grow during development, and why do they fail to regrow when injured? In the complicated mesh of our nervous system, the axon is the information superhighway, carrying all of the data we use to sense our environment and carry out behaviors. To wire up our nervous system properly, neurons must elongate their axons during development to reach their targets. This is no simple task, however. The complex morphology of axons and dendrites puts neurons among the most intricate and beautiful cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(145 citation statements)
references
References 184 publications
4
139
1
1
Order By: Relevance
“…Interestingly, it is still unknown whether postnatal ON axonal growth occurs as a diffuse phenomenon, or whether there is a specific focal site (for example, at the junction of the eye and ON). 5 Because the majority of ON growth occurs by 3 years of age, this postnatal interval likely represents a period of increased sensitivity and potential damage. Conversely, the factors associated with postnatal growth of the human ON may also increase early resistance and recovery to ON stressors such as elevated IOP, compared with treatment in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is still unknown whether postnatal ON axonal growth occurs as a diffuse phenomenon, or whether there is a specific focal site (for example, at the junction of the eye and ON). 5 Because the majority of ON growth occurs by 3 years of age, this postnatal interval likely represents a period of increased sensitivity and potential damage. Conversely, the factors associated with postnatal growth of the human ON may also increase early resistance and recovery to ON stressors such as elevated IOP, compared with treatment in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Although ribosomes, HuD, and GAP-43 mRNA have been detected in axonal growth cones [86], this may be a secondary site of synthesis, as axonal protein synthesis does not appear to be necessary if protein synthesis in the cell body is available [105]. It is nevertheless possible that local protein synthesis is necessary to provide growth-related proteins that sensitize the growth cone to guidance cues [35]. It has been shown that inhibitors of protein synthesis prevent the turning of retinal growth cones in response to chemotropic agents such as netrin-1 [14].…”
Section: Synthesis Of Gap-43mentioning
confidence: 99%
“…The fact that this does not occur in the central nervous system has been attributed to an inhibitory glial environment as well as to a loss of both intrinsic and extrinsic factors [35]. In adult mammals, retinal ganglion cells cannot regenerate their axons after optic nerve injury, and they subsequently undergo apoptotic cell death [52].…”
Section: Gap-43 Neurotrophins Cell Adhesion Molecules Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Od tada je u brojnim studijama pokazano da BDNF ojačava ekscitatorne (glutamatne) sinapse i oslabljuje inhibitorne (GABAergičke) sinapse. Kang i Schuman (1995) (Goldberg, 2003). U ove stimuluse spadaju neurotrofini, vanćelijski matriksni molekuli laminin, heparan sulfat proteoglikani, kao i ćelijski adhezivni molekuli kao što su L1 i N-kadherin (Goldberg, 2003).…”
Section: Regulacija Sinaptičke Plastičnosti Putem Neurotrofinaunclassified